Patterns of Pesantren Strength in Facing the Hegemony of Modernity - Supriyanto, Supriyanto; Bahri, Samsul; Ghifari, Ahmad (Pascasarjana IAIN Sultan Amai Gorontalo, 2025)
This study aims to analyze the patterns of pesantren so that they can stand firm in the face of the hegemony of modernity. The research uses an analytical descriptive method with an educational history and sociology approach. This study proves that pesantren have the following strengths: (1) having a tradition of scientific rihlah, writing, and reading the yellow book. (2) having kiyai leadership, (3) educational patterns in pesantren, (4) pesantren are in accordance with social theory in organisations, consisting of adaptation, the system must adapt to the environment, and adapt the environment to needs. As for what underlies the pattern, there is Goal Attainment, a system that must define and achieve its main goals. Integration, Latency (pattern maintenance). This strength is what makes pesantren strong.